Method for Increasing the Humidity in Polymer Electrolyte Membrane Fuel Cell. Issue 2 (1st February 2016) - Carello, M.; Vita, A. De; Ferraris, A.
Abstract: The water content within the polymer electrolyte membrane is essential to have good proton conduction and high efficiency of a fuel cell system. In this paper a new technique to increase the fuel cell efficiency acting on the internal humidity will be presented. In order to understand the potentialities and the limitations of such technique, the method was studied in a theoretical approach and then applied on a proton exchange membrane fuel cell (1 kW PEMFC) that supplies the energy for the traction of a prototype vehicle, which took part in the last Shell Eco‐marathon competition. Finally has been verified that the membrane water content is related to the hydrogen consumption and for some applications ( e.g., military single‐use equipment), the "filling" method could be advantageous over humidified system and non‐humidified systems. To ensure the proper success of the procedure it is also applied the differential method to fault detection.